Fractalkine-induced activation of the phosphatidylinositol-3 kinase pathway attentuates microglial activation in vivo and in vitro. - LYNCH, AILEEN; LYNCH, MARINA (My University, 2009)
Several neurodegenerative disorders are associated with evidence of inflammation, one feature of which is increased activation of microglia, the most likely cellular source of inflammatory cytokines like interleukin-1b. It is now recognized that interaction of microglia with other cells contributes to maintenance of microglia in a quiescent state and the complementary distribution of the chemokine, fractalkine (CX3CL1) on neurons and its receptor (CX3CR1) on microglia, suggests that this interaction may play a role in modulating microglial activation. Here we demonstrate that both soluble and membrane-bound fractalkine attenuate lipopolysaccharide- induced microglial activation in vitro. We also show that fractalkine expression is reduced in the brain of aged rats and this is accompanied by an age-related increase in microglial activation. Treatment of aged rats with fractalkine attenuates the age-related increase in microglial activation and the evidence indicates that fractalkine-induced activation of the phosphatidylinositol-3 kinase pathway is required to maintain microglia in a quiescent state both in vivo and in vitro.
PUBLISHED
Keywords: Neuroscience; cytokines; fractalkine expression; Immunology, Inflammation & Infection; Neuroscience